Finding a deeper understanding of the intersection among trauma, social-emotional learning, and dropping out: a phenomenological study - Zerr, Donna (Kansas State University, 2020)
The purpose of this phenomenological interview study was to examine the lived experiences of five childhood trauma survivors who dropped out of high school in central Kansas within the past three years but eventually decided to pursue their diploma in an adult learning center. With the state of Kansas implementing the Kansans CAN (2015) initiative, which emphasizes social-emotional learning and high school graduation, this qualitative study explores the intersection of trauma, social-emotional learning, and dropping out. Using purposeful sampling and in-depth interviews, the participants shared their lived experiences at home, in school, and the community as it relates to their ultimate decision to discontinue their schooling. The results of this study deepen our understanding of how trauma and social-emotional learning played significant roles in the participants’ decisions to leave school. However, specifically they revealed how deep relationships and emotional connections factored into their decisions to pursue a high school diploma. This study elevates conversations about the need to articulate the strengths and differences found in the implementation of social-emotional curricula and trauma-informed teaching in schools. Additionally, the participants’ stories support the need for more profound levels of emotional connectedness with traumatized students in schools and raise questions about how much teachers are prepared for or feel comfortable with – building those kinds of relationships with their students.
Keywords: social-emotional learning; trauma; adverse childhood experiences; high school dropouts; high school graduation; Kansas